Potential of Transdermal Hormonal Contraception in Indonesia: A Systematic Literature Review - Ulfa Nadia Nurul Firdaus; Nurul Wahidah; Yulianti Hayati; Aryl Alfath Muhammad Iqbal; Dhiny Isma (Jurnal Kesehatan, 2026)
Indonesia is one of the most populous countries in the world. Projections indicate that Indonesia's population will reach 321 million by 2045. One effort to curb population growth is through the Family Planning (FP) program. Transdermal hormonal contraceptive methods have been developed, offering advantages such as more efficient, painless administration, reduced biohazardous waste, and innovative and practicality. This study analyzes the potential of transdermal hormonal contraceptive methods to support efforts to curb growth in Indonesia. This study, using a systematic review, was conducted with the PICO framework. A systematic review was conducted by searching the literature from 2020 to 2025 in two academic databases: ScienceDirect and PubMed. Of the 384 initial articles identified, 4 met the criteria and were analyzed to extract relevant findings on transdermal hormonal contraceptives. The review revealed that transdermal contraceptives have significant potential to reduce birth rates and unplanned pregnancies due to their effectiveness and convenience. However, their adoption is heavily influenced by education, counseling quality, family planning service policies, and equitable access. In Indonesia, the use of transdermal/patch contraceptives remains low due to their relatively high price, exclusion from free family planning services, and the need for a doctor's prescription. Furthermore, many healthcare professionals are unfamiliar with its effectiveness and benefits and therefore rarely recommend it. These findings provide a valuable roadmap for policymakers and healthcare professionals in Indonesia to receive adequate training and keep up to date with the latest knowledge to become more confident in recommending this method.